Eksplorasi Peran Museum Kota Lama Semarang : Tinjauan Arsitektural dan Estetika Seni - Rona Fajar Imawan; Istiqomah Musyafa Laela (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The research explores the role of Semarang Old Town Museum in the context of architecture and art aesthetics, which are important elements in the preservation of local cultural history, this study aims to understand how museums also become a medium for historical education and foster historical appreciation to urban communities. The Museum of the Old City of Semarang not only functions as a historical exhibition space, but also as an iconic identity of the community through the building design and aesthetics of the building that is very attractive. Through architectural elements and aesthetic rules of art with a classic building style using brick matrial that can strengthen the attractiveness of tourists and culturists on the importance of awareness and the importance of preserving historical landmarks. Therefore, this museum plays a significant role in shaping the image of the old city of Semarang, becoming one of the cultural and artistic tourist destinations.